ANALISIS DETERMINAN PENDAPATAN RUMAH TANGGA MISKIN DI KECAMATAN KARANGASEM - Wiguna, I Nyoman Bayu Sugiarta; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021DO - 10.24843/EEB.2021.v10.i08.p06, 2021)
Poverty is the biggest challenge faced by the world and is one of the three main problems that exist in economic development in the world. This study aims to analyze the effect of education, age, and work participation of family members simultaneously and partially on the income of poor households in Karangasem District. This research was conducted in Karangasem sub-district with a total sample of 100 respondents using the sampling method, namely proportionate random sampling and data collection methods, namely observation, structured interviews, and in-depth interviews. The data analysis technique used is multiple linear regression. The results of this study indicate that the variables of education, age, and the level of work participation of family members simultaneously have a significant effect on the income of poor households in Karangasem District. The variables of education, age, and participation level partially have a positive and significant effect on the income of poor households in Karangasem District.